Sensibilidade e fruição na obra Totalidade e infinito de Emmanuel Levinas - Ferreira, Frederico Santos (2017)
The purpose of this dissertation is to present Emmanuel Levinas (1906-1995) conception the concept of sensibility and fruition in the work, Totality and Infinity: an essay on exteriority of 1961.We will try to understand its unintentional movement which takes the sensibility as an element human being that animates consciousness as the intentionality of fruition in this way the conduction of the research will have as problematic interior life of the Levinasian subject, that is his immanence. Thus we need to understand the criticism that the author makes philosophy based on a representation, on the objectification of knowledge. The world in which we live is not given to us as a tool, but as food, because we enjoy the world, from living and not from the consciousness of our relationship with the world is a first experience, therefore, the need of the body, indigent and naked makes us go out in search of the satisfaction, the joy that comes from the mouth. The valorization of the selfhood of the self that takes the affection as the constructor of human subjectivity, defining sensibility as an element of feeling and not of experience. Therefore, it is necessary to rethink the philosophy that is constituted from an absolute self, philosophy of the same, objectification of knowledge, to a philosophical knowledge that is open, always current, that values the sensitive presence, next to the elements. In this way, we must understand the human being as a separate subject, which enjoys as a single subject, sensibility always exposed to the possibility of happiness.